Otimização de uma fórmula para obtenção do creme de queijo coalho com adição de hidrocoloides e extrato de manjericão (Ocimum basilicum L.) - Teles, Alan Rodrigo Santos (2019)
Coalho cheese is widely consumed in the Northeast of Brazil, being substantially important for the local economy. Despite the worldwide technological evolution, its production is usually handmade, making it difficult for the consumer to consume it because new consumers are looking for differentiated products with added value such as cream cheese. But consumers as well as seeking innovative products are looking for healthier products, such as cream cheese light. The reduction of fat in cheeses causes changes in the organoleptic characteristics, and to minimize these changes it is necessary to use fat substitutes such as hydrocolloids. But cheeses even with reduced fat content are subject to oxidative reactions, and these reactions reduce nutritional value, alter sensorial characteristics and produce compounds harmful to health. To inhibit the lipid oxidation of dairy products synthetic antioxidants are usually employed, but their consumption has harmful effects on health, which is why natural sources have started to be studied. Natural antioxidants are usually used in food as an extract, among the extracts with antioxidant action we have the basil extract (Ocimum basilicum L). Thus, the objective of the work was to develop coalho cheese cream added with hydrocolloids (gelatin, xanthan gum) and to add basil extract to coalho cheese that presented greater stability. Coalho cheese creams were obtained according to the conditions of the Central Compound Design type 2². The dependent variables were %hydrocolloid (gelatin or xanthan gum) and temperature and as independent variables %moisture, %EST, %Fat, pH, %acidity, firmness and adhesiveness. To evaluate the stability of the optimized rennet cheese creams, the abovementioned analyzes were carried out for 15 days. The optimization of the conditions of obtaining the basil extract was obtained according to the conditions of the Central Rotational Compound Design type 2², with the independent variables being ethanol concentration and the extraction temperature and as dependent variables phenolic, total flavonoid and antioxidant capacity against the radicals ABTS and DPPH. The hydrocolloid content (gelatin, xanthan gum) was the variable that most influenced the characteristics of rennet cheese cream. For the determination of the shelf life of the cheese cream added with xanthan gum and basil extract the same analyzes of the cream of cheese added of hydrocolloids were performed in addition to the analyzes of %protein and total coliforms. The coalho cheese cream added with xanthan gum presented greater stability. The concentration of ethanol and temperature had a significant influence (p <0.05) on phenolic, total flavonoid and antioxidant capacity. In the optimal condition, the extract had phenolic, total flavonoid content of 425.53 ± 3.28 mg GAE / g dry extract, 265.48 ± 7.55 mg QE / g dry extract and antioxidant capacity of 9004.68 ± 117.19 μmol TE / g dry extract and 0.5902 ± 0.0634. The addition of the basil extract to the coalho cheese cream added with xanthan gum increased the shelf life.